Stabilnost terapevtskih proteinov - Temova Rakuša, Žane (Farmacevtski vestnik, 2018)
Biopharmaceuticals represent an important class of pharmaceuticals that are widely used in clinical practice. Compared to traditional synthetic active ingredients, peptide and protein molecules are substantially larger with more complex structure. Because of their unique three dimensional structures and many functional groups, therapeutic proteins are susceptible to various degradation mechanisms, which can be divided in two general classes: chemical and physical instability. The most common form of physical instability is denaturation with subsequent aggregation, precipitation and surface adsorption. Chemical instabilities include oxidation, deamidation and other less frequent reactions. Both types of instability can increase the likelihood of adverse immunogenic effects and/or result in a decreased biological activity. Therefore, characterization of instability mechanisms is a critical part of quality assurance process. The article summarizes the most common degradation mechanisms and factors, which affect proteins stability and also discusses appropriate approaches towards protein stabilization.
Keywords: Biološka zdravila; drug; nestabilnost; stabilizacija; terapevtski proteini; Zdravila